DEVELOPING E-LEARNING BASED ENGLISH MATERIAL FOR THE TENTH GRADE OF ARCHITECTURE ENGINEERING DEPARTMENT STUDENTS OF SMKN BALI MANDARA - Sita Dewi, Nope Luh; Ratminingsih, Ni Made; Piscayanti, Kadek Sonia (Lingua Scientia, 2021)
This study was a research and development (R&D) which aimed at finding out kinds of supplementary materials, design, and quality of English materials that are required for teaching the tenth grade of architecture engineering department students at SMKN Bali Mandara. The developed material was designed under the Research and Development (R&D) model by Richey and Klein (2007) that involved three processes, namely Design, Development, and Evaluation. The developed materials were identified based on syllabus analysis of 5 (five) English learning topics; announcement, transactional interaction texts, recount text, narrative text, and song lyrics. According to the result of material design identification, in every chapter, it should be completed with the title of the chapter, studentsâ€™ competency, learning indicators, learning objectives, learning material, and assessment part. The developed material was assessed by three expert judges. The expert judgesâ€™ assessment criteria used were based on eight principles in developing good material for English for Specific Purposes (ESP) by Widodo and Pusporini (2010). Those principles are clear goals, learning tasks, studentsâ€™ interest-based tasks, communication-based tasks, integrated language skills materials, original learning materials, impactful learning materials, and a good role model to be used outside classrooms. The result of the expert judgesâ€™ assessment showed that the product was categorized as â€œExcellentâ€ with a total score of 206. It indicates that this product is applicable for the teacher to improve the teaching-learning process for the tenth grade of Architecture Engineering Department students of SMKN Bali Mandara.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Keywords: e-learning materials, need analysis, ESP, architecture engineering department.